2017
DOI: 10.15294/jpii.v6i1.7205
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Science Domain Based Learning Media Which is Integrated with Local Potention to Improve Science Process Skill and Scientific Attitude

Abstract: This research was conducted to: (1) improve the science domain based learning tool which is integrated with appropriate local wisdom for Science learning material "Object Change Around Us" for students grade VII of Junior High School, (2) know the effectiveness of science based learning tool which is integrated with developed local wisdom to improve science process skill and scientific attitude of students grade VII of Junior High School. This research was a research and development which adapt 4D Thiagarajan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 8 publications
4
65
0
14
Order By: Relevance
“…Based on the result of data analysis, it was found that the methods that can be developed for Physics are inquiry/investigation method (mean=4.75), discussion/question and answer (mean=4.63), and demonstration (mean=4.38). The most appropriate method to be developed is investigation/ inquiry.Inquiry method is the most appropriate for developing science process, critical thinking, and scientific atttitudes or scientific charatter (Hairida, 2016;Harlen, 1992;Neuby, 2010;Sumaji, 1998;Suastra et al, 2011;Neka et al, 2015;Trowbridge & Bybee, 1990;Wenning, 2005;Priyantini et al, 2015;Alpusari & Putra, 2015;Dwianto et al,2017). Thus, Physics teaching does not only focus on the conceptual, process, and application dimensions, but it has developed the extention of the science education dimensions, i.e., to positive attitude, creativity, and the nature of science itself.…”
Section: 83mentioning
confidence: 99%
“…Based on the result of data analysis, it was found that the methods that can be developed for Physics are inquiry/investigation method (mean=4.75), discussion/question and answer (mean=4.63), and demonstration (mean=4.38). The most appropriate method to be developed is investigation/ inquiry.Inquiry method is the most appropriate for developing science process, critical thinking, and scientific atttitudes or scientific charatter (Hairida, 2016;Harlen, 1992;Neuby, 2010;Sumaji, 1998;Suastra et al, 2011;Neka et al, 2015;Trowbridge & Bybee, 1990;Wenning, 2005;Priyantini et al, 2015;Alpusari & Putra, 2015;Dwianto et al,2017). Thus, Physics teaching does not only focus on the conceptual, process, and application dimensions, but it has developed the extention of the science education dimensions, i.e., to positive attitude, creativity, and the nature of science itself.…”
Section: 83mentioning
confidence: 99%
“…The tradition is maintained because the people believed in the truth of genuine knowledge. Indigenous knowledge that has been converted into a science or science can enrich teaching materials (Wang & David, 2002;Lee et al, 2012;Kidman et al, 2013;Dwianto et al, 2017).…”
Section: Figure 3 Map Location Of Indigenous Knowledge Exploration Imentioning
confidence: 99%
“…It is conducted based on local wisdom in the surroundings. Ethnoscience is given to students to integrate original knowledge as an integral part of science learning (Andriana et al, 2017;Dwianto et al, 2017;Hartini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there was also no study combining the learning model with Papua local culture as a form of ethnoscience to conduct physics learning more contextually. Other studies had not revealed Papua local culture yet as they have elaborated on other islands in Indonesia (Andriana et al, 2017;Dwianto et al, 2017;Hartini et al, 2018). Also, based on the preliminary study, teachers in Papua needed a new learning model in physics teaching and learning.…”
Section: Introductionmentioning
confidence: 96%